INCIDENCE AND DETECTION OF PLEUROPNEUMONIA-LIKE ORGANISMS IN CELL CULTURES BY FLUORESCENT ANTIBODY AND CULTURAL PROCEDURES - Barile, Michael F. (1962)
Barile, Michael F. (National Institutes of Health, Bethesda, Md.), Walter F. Malizia, and Donald B. Riggs. Incidence and detection of pleuropneumonia-like organisms in cell cultures by fluorescent antibody and cultural procedures. J. Bacteriol. 84:130–136. 1962—A total of 102 tissue-cell cultures from 17 separate laboratories was examined for pleuropneumonia-like organisms (PPLO) by the fluorescent antibody and cultural procedures. PPLO were isolated from 48 of the 49 tissue-cell cultures found positive for PPLO by the fluorescent antibody procedure, and results of the two procedures agreed in 101 of the 102 (99%) cases. PPLO were isolated from none of 10 primary-cell cultures prepared from six animal species and from 48 of 92 (52%) continuous-cell cultures prepared from eight animal species. Cells grown in media containing antibiotics were more frequently contaminated with PPLO (72%) than cells grown in antibiotic-free media (7%). Cultures (91%) from tissue-culture-producing laboratories and cultures (76%) used for propagation of microorganisms were contaminated with PPLO, although none used for tissue-culture metabolic studies was contaminated. In addition, our findings support the view that PPLO contamination of cell cultures is probably owing to bacterial contaminants which revert to L forms in the presence of antibiotics.